Analisis Praktek Qardh bagi Petani Jagung di Nagari Salareh Aia Timur, Kecamatan Palembayan, Kabupaten Agam Perspektif Ekonomi Islam - Sindi Saputri; Endri Yenti (Lembaga Yasin AlSys, 2026)
This study was motivated by the practice of qardh accompanied by the provision that corn farmers who borrow must pledge their corn fields to the toke, are required to sell their harvest to the lender, face differences in purchase prices between indebted and non-indebted farmers, and are subject to the toke taking profit from the sale of harvested corn per ton. This study aims to describe the practice of qardh in Nagari Salareh Aia Timur and to analyze it from the perspective of Islamic Economics. This study used a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through the stages of data collection, data reduction, and conclusion drawing. The results showed that the practice of qardh between corn farmers and toke in Nagari Salareh Aia Timur was generally influenced by economic factors and the limited access to transportation for farmers to reach the corn fields. The practice of qardh was not entirely based on the spirit of mutual assistance, but was instead accompanied by certain interests that bound the farmers. The contract used took the form of a verbal agreement covering all loan provisions. From the perspective of Islamic Economics, the application of Islamic economic principles in this practice has not been fully implemented, because corn farmers have applied only some of the existing principles. This study concludes that the practice of qardh taking place in Nagari Salareh Aia Timur still leaves problems in the application of Islamic Economic principles, particularly in relation to justice, public benefit, and the orientation of mutual assistance in lending transactions.